2012
DOI: 10.3386/w18457
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Targeting of Treatment: Evidence from College Remediation

Abstract: At an annual cost of roughly $7 billion nationally, remedial coursework is one of the single largest interventions intended to improve outcomes for underprepared college students. But like a costly medical treatment with non-trivial side effects, the value of remediation overall depends upon whether those most likely to benefit can be identified in advance. Our analysis uses administrative data and a rich predictive model to examine the accuracy of remedial screening tests, either instead of or in addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
142
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(145 citation statements)
references
References 3 publications
2
142
1
Order By: Relevance
“…In response, some states and institutions have reformed assessment and placement strategies. Changes included simplifying the testing process by requiring institutions to use common assessments and cut scores; using additional measures to determine placement; enhancing information on the importance of the assessment; and offering test preparation for the assessment (Barnett and Reddy, 2017;Rodriguez, 2014;Scott-Clayton, Crosta, and Belfield, 2012). …”
Section: A Movement To Refor M Developmental Educationmentioning
confidence: 99%
“…In response, some states and institutions have reformed assessment and placement strategies. Changes included simplifying the testing process by requiring institutions to use common assessments and cut scores; using additional measures to determine placement; enhancing information on the importance of the assessment; and offering test preparation for the assessment (Barnett and Reddy, 2017;Rodriguez, 2014;Scott-Clayton, Crosta, and Belfield, 2012). …”
Section: A Movement To Refor M Developmental Educationmentioning
confidence: 99%
“…Higher education scholars have documented how variables such as high school GPA and prior course-taking are often stronger predictors of college success than test scores (Adelman, 2006;Armstrong, 2000;DesJardins & Lindsey, 2007). Challenging the over-reliance on placement testing, researchers have also found that supplementing or even replacing placement tests with high school transcript (HST) information may improve course placement (Ngo & Kwon, 2015;Scott-Clayton, Crosta, & Belfield, 2014). Further, math diagnostics can also be a potentially valuable resource for math faculty and student support center personnel.…”
Section: Using High School Transcript Data and Diagnostic Informationmentioning
confidence: 99%
“…One way to make this determination is to estimate the rate of successful placement and erroneous placement in each A&P context, following procedures described in Sawyer (1996;2007) and most recently by Scott-Clayton et al (2014). The estimation strategy results in the overall proportions of students placed successfully and students placed in error for each level of math.…”
Section: Improving Math Placementmentioning
confidence: 99%
See 2 more Smart Citations